Hubungan Kerja Sama Perdagangan Komoditas Batu Bara Indonesia-China Tahun 2014-2021: Hubungan Kerjasama Perdagangan Komoditas Batubara Indonesia-China Tahun 2014-2021 - Nurul Penti; Y. A. Wahyudin; Ahmad Mubarak Munir (Indonesian Journal of Global Discourse, 2022)
This research aims to explain the relationship of bilateral trade cooperation between Indonesia and China in coal commodities, the influencing factors and the opportunities and defiances of Indonesia in trade cooperation of coal energy with China during the period of President Joko Widodo’s administration in 2014-2021. Indonesia and China are two countries that have very close relations in the energy sector, as seen from a lot of policies and cooperation agreed upon by the two countries. However, the existing social, economic and political dynamics also affect the cooperation between the two countries. Seeing these dynamics, this research tries to answer the reason why Indonesia and China did the coal trade cooperation, how was the bilateral cooperation between the two countries and what is Indonesia’s opportunity and defiance of coal bilateral trade cooperation with China. This research uses the Heckscher-Ohlin international trade theory, international cooperation and new trade strategy concepts to answer the questions. The data collection technique used in this research is a secondary data collection technique with a  literature review method. From the analysis, the coal bilateral trade cooperation between Indonesia-China does not escape from their national interest which is over production of coal in Indonesia and the lack of domestic coal energy resources in China. So the author concludes that domestic and global factors, big opportunities and defiances play a very important role in relation to coal bilateral trade cooperation between Indonesia and China.